The role of connectivity for accelerating ASEANâIndia economic integration - Negara, Siwage Dharma (P2E-LIPI, 2012)
Connectivity is one of the key factors that are important to accelerate economic integration betweenASEAN and India. Improved connectivity is critical to increase ASEANâIndia economic relationsand to strengthen ASEANâIndiaâs share in regional and global production networks. To buildand strengthen this connectivity, several strategic measures are needed. First, there is a need for a clearregional connectivity framework, a multi-modal, multi-functional and multi-tier approach, whichincludes land, maritime and air connectivity. Second, there is a need to establish strong regional institutionsfor cooperation in terms of planning, managing and funding the infrastructure needs. Third,ASEAN and India need to address wide infrastructure variations within their member countries andstates. Specifically, significant resources and time must be dedicated to build and strengthen infrastructurein Myanmar and the northeastern region of India, given their strategic location as the connectingnodes of ASEANâIndia connectivity. For infrastructure development, there must be a clear strategyto encourage more private sector participation. Publicâprivate partnership seems not only promisingbut also challenging given the complexity and cost of infrastructure investment. A fair distribution ofrisk remains a big constraint to the promotion of publicâprivate partnerships. Fourth, ASEANâIndiaconnectivity should be integrated with regional development plans and linked to the internationalproduction network. And finally, there is a need for strong political commitment to execute most of thepolicies and strategies that have been agreed to by the ASEAN countries and India.Keywords: Connectivity, Transport, Regional integration, ASEAN, India